COMPARATIVE PHYTOCHEMICAL SCREENING AND ANTIOXIDANT PROPERTIES OF IN VITRO AND IN VIVO PROPAGATED ORTHOSIPHON STAMINEUS BENTH (LAMIACEAE). - SHEENA, EDACHERY VEETIL; JOTHI, GABRIEL JEYA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Present study aims in in vitro propagation of the valuable medicinal plant, Orthosiphon stamineus in various concentrations of plant growth regulators and to compare the antioxidant activity and phytochemical contents of wild and in vitro cultivated O. stamineus. Method: Explants were cultured on Murashige and Skoog's medium supplemented with different concentrations of 6-benzyl amino purine (BAP) and Kinetin (KIN). The multiple shoots were subcultured in BAP (1.0 mg/l) and KIN (2.0mg/l). The leaf powder of wild and in vitro plants were subjected to sequential extraction using hexane, chloroform and ethanol. Preliminary phytochemical analysis and antioxidant activity of the leaf extracts of wild and in vitro cultivated plants were carried out. Antioxidant assay was performed using DPPH free radical scavenging and Hydrogen Peroxide scavenging methods. Results: Rapid multiple shoot growth (90%) was observed in Murashige and Skoog's (MS) medium with 1.0 mg/l BAP and 2.0 mg/l KIN. The results showed that the ethanol extract of the in vitro regenerated plantlets and the wild plant contained carbohydrates, tannins, quinones, phenols and coumarin. Chloroform extract of the in vitro regenerated plantlets showed strong DPPH radicals scavenging activity with % of Inhibition of 81.10 µg/mL compared to the wild plant extracts with % of Inhibition of 69.22 µg/mL. Similarly the ethanol extract of the in vitro regenerated plantlets showed strong scavenging activity with % of Inhibitionof 65.14 µg/mL compared to the wild plant extracts with % of Inhibitionof 40.46 µg/mL. Conclusions: The results indicated that in vitro regenerated plantlets exhibited excellent free radical scavenging activity and reducing activity compared to the extracts obtained from wild plants.